Peningkatan Hasil Belajar PAK melalui Model PBL pada Materi Budaya Kasih Kelas XI - A.Yoyok Ariwihandoyo; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research was motivated by the low learning outcomes of students at SMA Negeri 1 Kota Gajah, particularly in the subject of Catholic Religious Education and Character Education. Therefore, a classroom action research (CAR) was conducted to determine the extent to which the Problem Based Learning (PBL) model could improve the learning outcomes of Grade XI Phase F students on the topic “Developing a Culture of Love.” The study was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. In the first cycle, the evaluation results showed that only 3 students (37.5%) achieved mastery learning, while 5 students (62.5%) had not. Based on these results, an improvement action was conducted in the second cycle. The outcome of the second cycle showed a significant increase, with all students (100%) successfully achieving mastery learning. These findings indicate that the implementation of the PBL model effectively improves student learning outcomes on the topic “Developing a Culture of Love.” Thus, it can be concluded that the use of the Problem Based Learning (PBL) model not only enhances student learning outcomes but also successfully achieves the Minimum Competency Criteria (KKM) of 100% in Grade XI of SMA Negeri 1 Kota Gajah in the 2024/2025 Academic Year. The implementation of this method has proven effective and can serve as an alternative approach to improving the quality of Catholic Religious Education learning at the high school level.